Non-traumatic bilateral comminated acetabular fracture - Alsaeed, Abdullah A.; Alsaeed, Abdullah Y. (International Journal of Advances in Medicine, 2021)
High-energy trauma has been confirmed as a cause of bilateral acetabular fracture. However, there are few reports on nontraumatic bilateral acetabular fracture. We report a case of bilateral acetabular fracture that occurred acutely with no preceding trauma in a 50-year-old man with osteoporosis. The case shows the significance of regular annual calcium and vitamin D screening of patients at a high risk of pathological fracture.